Clinical and genetic factors associated with radiographic damage in patients with ankylosing spondylitis. Issue 4 (21st December 2022) - Nam, Bora; Jo, Sungsin; Bang, So-Young; Park, Youngho; Shin, Ji Hui; Park, Ye-Soo; Lee, Seunghun; Joo, Kyung Bin; Kim, Tae-Hwan
Abstract : Objectives: To identify clinical and genetic factors associated with severe radiographic damage in patients with ankylosing spondylitis (AS). Methods: We newly generated genome-wide single nucleotide polymorphism data (833K) for 444 patients with AS. The severity of radiographic damage was assessed using the modified Stoke Ankylosing Spondylitis Spinal Score (mSASSS). To identify clinical and genetic factors associated with severe radiographic damage, multiple linear regression analyses were performed. Human AS-osteoprogenitor and control-osteoprogenitor cells were used for functional validation. Results: The significant clinical factors of final mSASSS were baseline mSASSS (β=0.796, p = 3.22×10 −75 ), peripheral joint arthritis (β=−0.246, p = 6.85×10 −6 ), uveitis (β=0.157, p = 1.95×10 −3 ), and smoking (β=0.130, p=2.72×10 −2 ) after adjusting for sex, age and disease duration. After adjusting significant clinical factors, the Ryanodine receptor 3 ( RYR3 ) gene was associated with severe radiographic damage (p=1.00×10 −6 ). For pathway analysis, the PI3K-Akt signalling pathway was associated with severe radiographic damage in AS (p=2.21×10 −4, false discovery rate=0.040). Treatment with rhodamine B, a ligand of RYR3, dose-dependently induced matrix mineralisation of AS osteoprogenitors. However, the rhodamine B-induced accelerated matrix mineralisation was not definitive in control osteoprogenitors. Knockdown of RYR3 inhibited matrix mineralisation in SaOS2 cell lines. Conclusions: This study identified clinical and genetic factors that contributed to better understanding of the pathogenesis and biology associated with radiographic damage in AS.